When I say … neurodiversity paradigm - Shaw, S.C.K.; Brown, M.E.L.; Jain, N.R.; George, R.E.; Bernard, Sarah; Godfrey-Harris, M.; Doherty, M. (2025)
In this “When I say…” article, the authors argue for a philosophical transformation in how medical education values different ways of thinking and learning: the neurodiversity paradigm.